Surface texturing on dry-lubricated transmissions and power systems to deliver better performance and simplified systems in aerospace engineering - Ding, Liang (2021)
Dry-lubricated contact systems are widely used in varied engineering applications, among which the spherical plain bearing (with dry-lubricating liner) in aerospace applications is one with increasing demands in performance. To achieve the improvements, the surface texturing is a propitious technique since it has seen a rapid development in the last few decades as it achieved promising effects in friction, wear and adhesion with different forms. However, to tailor the surface textures to the needs in tribological performance, it is essential to fill the gap of knowledge in the aspects such as the interaction between the liner surface and the textured counterface and the influence of the kinematics of the transmission system. Meanwhile, the relationship between the bonding strength of the liner and texturing morphology and adhesion force needs to be investigated.